Effect of size on the eccentric compression performance of damaged square RC columns strengthened with CFRP: An experimental study. Issue 1 (January 2023) - Si, Jianhui; Li, Kai; Zeng, Zhaobao; Liu, Zewei; Hu, Jiannan
The objective of this study was to experimentally analyze the effect of size on the eccentric compression performance of damaged square Reinforced concrete (RC) columns reinforced with Carbon Fiber Reinforced Plastic (CFRP) in a bid to improve the rationality of the design of CFRP-reinforced large concrete members. In the experiment, 18 square RC columns with proportional sizes were prepared, and the principle of the proportional changes in the size was strictly controlled. The effects of the size, eccentricity, pre-damage, and number of CFRP layers were considered in the experiment, and the bearing capacity, lateral deflection, rebar strain, CFRP strain, and failure modes of RC columns of different sizes before and after the reinforcement were studied. The experimental results showed that the CFRP reinforcement could improve the bearing capacity and deformability of damaged square RC columns under small eccentric compression; however, the reinforcement effect gradually decreased with increasing size. When the cross-sectional dimensions were 100, 200, and 300 mm, the bearing capacity increased by 26.17%, 17.27%, and 12.98%, respectively, and the ductility coefficient increased by 104%, 44.80%, and 35.20%, respectively.